2004
DOI: 10.1088/1367-2630/6/1/144
|View full text |Cite
|
Sign up to set email alerts
|

Implications evinced by the phase diagram, anisotropy, magnetic penetration depths, isotope effects and conductivities of cuprate superconductors

Abstract: Anisotropy, thermal and quantum fluctuations and their dependence on dopant concentration appear to be present in all cuprate superconductors, interwoven with the microscopic mechanisms responsible for superconductivity. Here we review anisotropy, in-plane and c-axis penetration depths, isotope effect and conductivity measurements to reassess the universal behavior of cuprates as revealed by the doping dependence of these phenomena and of the transition temperature.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 94 publications
(175 reference statements)
0
18
0
Order By: Relevance
“…This is consistent with the generic behavior for high-temperature superconductors, where for a given HTS family T c increases with reduced aniostropy. 10,13,14 Although these changes are small compared to those in the critical amplitudes of the in-plane penetration depth ∆λ abo /λ abo and the correlation lengths ∆ξ ab0 /ξ ab0 , ∆ξ c0 /ξ c0 (see Table I) it becomes clear that the pressure induced change of the anisotropy is the essential ingredient which remains to be understood microscopically. Empirically the anisotropy decreases rather steeply by approaching optimum doping and levels off in the overdoped regime.…”
Section: Fig 2: Magnetization Data Rescaled According Tomentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with the generic behavior for high-temperature superconductors, where for a given HTS family T c increases with reduced aniostropy. 10,13,14 Although these changes are small compared to those in the critical amplitudes of the in-plane penetration depth ∆λ abo /λ abo and the correlation lengths ∆ξ ab0 /ξ ab0 , ∆ξ c0 /ξ c0 (see Table I) it becomes clear that the pressure induced change of the anisotropy is the essential ingredient which remains to be understood microscopically. Empirically the anisotropy decreases rather steeply by approaching optimum doping and levels off in the overdoped regime.…”
Section: Fig 2: Magnetization Data Rescaled According Tomentioning
confidence: 99%
“…Empirically the anisotropy decreases rather steeply by approaching optimum doping and levels off in the overdoped regime. 10,13,14 Together with Eq. (6) this explains why the pressure effect on T c becomes very small in optimally and overdoped cuprate superconductors.…”
Section: Fig 2: Magnetization Data Rescaled According Tomentioning
confidence: 99%
See 1 more Smart Citation
“…There is considerable evidence that cuprate superconductors with moderate anisotropy exhibit in zero field 3D-xy critical behavior [11,12,13,14,20,22,23,24,36,37,38,39,40,41,42,43,44]. The critical exponents are then given by [45,46] …”
mentioning
confidence: 99%
“…Theoretical calculations revealed that the logarithmic temperature dependence of the resistivity is expected in granular metals because of the Coulomb interaction [33,34]. Furthermore, analysis of the temperature dependence of the magnetic-field penetration depth λ in different cuprate superconductors shows a finite-size effect on λ, revealing the existence of superconducting nanoscale domains [35]. The observed oxygen isotope effect (OIE) on the size of the superconducting domains clearly indicates the existence and relevance of the coupling between the superfluid and local lattice distortions [35].…”
mentioning
confidence: 97%